Importance of short-term temporal variability in soil physical properties for soil water modelling under different tillage practices - Geris, Josie; Verrot, Lucile; Gao, Lei; Peng, Xinhua; Oyesiku-Blakemore, Joseph; Smith, Jo U.; Hodson, Mark E.; McKenzie, Blair M.; Zhang, Ganlin; Hallett, Paul D. (Soil & tillage research, 2021)
•No-till and ploughed soil properties vary over short time with different trends.•Impacts on soil water model simulations were explored using HYDRUS 1-D.•Both natural and tillage induced changes in soil lead to differences in simulations.•Accounting for soil variations over a season is important for soil water simulations. Soil properties are often assumed to be static over time in hydrological studies, especially in hydrological modelling. Although it is well appreciated that soil structure and its impact on hydraulic properties are time-variable, particularly on cultivated land, very few studies have focused on quantifying the influence of such changes on soil hydrology, especially at the short term (i.e. seasonal). This study explored the value of incorporating such short-term time-variable soil properties in hydrological models. It is based on soil hydraulic properties from temporal field data under no-till done by direct seeding and under conventional cultivation done by ploughing to 0.2 m and harrowing. It uses a controlled tillage experiment in Scotland, on a soil with very good structural stability that experiences gentle rainfall in a temperate oceanic climate (Köppen Cfb). Water retention data were collected from intact soil cores sampled at 0.025, 0.095 and 0.275 m depth at three times between April and August 2013; (i) immediately following tillage, (ii) at barley crop establishment 1 month later and (iii) after harvest. Soil structure varied over time, with no-till soils gaining porosity and ploughed soils losing porosity. We hypothesised that no-till soils would have less seasonal temporal variability, but found it to be comparable to ploughed soils, albeit with pore structure changes following different trends. These changes were reflected in Van Genuchten fitting parameters, which if accounted for in 1-D HYDRUS modelling, had a marked impact on modelled soil water content over time if contrasted to predictions assuming a static pore structure. Using data from multiple sampling events, as opposed to one sampling event, resulted in up to a 44 % difference in soil water content predictions and increased the temporal variability by a factor of 1.5. Hence, our results have demonstrated that it is important to account for short-term temporal variability in soil physical properties in soil water modelling studies, and should not be ignored as a default, particularly on cultivated agricultural soils.